2023
DOI: 10.3164/jcbn.23-10
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of serum bile acid profile among traumatic brain injury patients: a small-scale prospective study

Abstract: Traumatic brain injury is one of the major causes of morbidity and mortality worldwide. With the development of bile acids as a potential treatment, to identify the influence of traumatic brain injury on bile acid metabolism shows growing importance. This present study did a preliminary exploration of the bile acid profile alteration among traumatic brain injury patients. In total, 14 patients and 7 healthy volunteers were enrolled. The bile acid profile of the blood samples were detected by an Ultra-performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…After brain injury, the mechanism of bile acid metabolism in the liver and brain changed (Huang et al 2015 ), and six hours later, the acute phase response (APR) of the liver and the inflammatory system were activated successively, which led to the imbalance of bile acid homeostasis in the brain (Nizamutdinov et al 2017 ). A recent prospective study had also confirmed that traumatic brain injury induces alterations in plasma bile acid metabolism and may lead to a drop in metabolic levels of glycocholic, taurocholic, and glycoursodeoxycholic (Zhu et al 2023 ). Additionally, the distribution of bile acid receptors and transporter proteins throughout the brain (especially on immune and glial cells) provided a theoretical basis for the possible regulation of neuronal function by bile acids (Bhargava et al 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…After brain injury, the mechanism of bile acid metabolism in the liver and brain changed (Huang et al 2015 ), and six hours later, the acute phase response (APR) of the liver and the inflammatory system were activated successively, which led to the imbalance of bile acid homeostasis in the brain (Nizamutdinov et al 2017 ). A recent prospective study had also confirmed that traumatic brain injury induces alterations in plasma bile acid metabolism and may lead to a drop in metabolic levels of glycocholic, taurocholic, and glycoursodeoxycholic (Zhu et al 2023 ). Additionally, the distribution of bile acid receptors and transporter proteins throughout the brain (especially on immune and glial cells) provided a theoretical basis for the possible regulation of neuronal function by bile acids (Bhargava et al 2020 ).…”
Section: Discussionmentioning
confidence: 86%